Combinatorial extracellular matrix microarray identifies novel bioengineered substrates for xeno-free culture of human pluripotent stem cells. (July 2020) - Ireland, Ronald G.; Kibschull, Mark; Audet, Julie; Ezzo, Maya; Hinz, Boris; Lye, Stephen J.; Simmons, Craig A.
Abstract: Stem cells in their microenvironment are exposed to a plethora of biochemical signals and biophysical forces. Interrogating the role of each factor in the cell microenvironment, however, remains difficult due to the inability to study microenvironmental cues and tease apart their interactions in high throughput. To address this need, we developed an extracellular matrix (ECM) microarray screening platform capable of tightly controlling substrate stiffness and ECM protein composition to screen the effects of these cues and their interactions on cell fate. We combined this platform with a design of experiments screening strategy to identify optimal conditions that can maintain human pluripotent stem cell (hPSC) pluripotency in chemically defined, xeno-free conditions. Combinations of ECM proteins (fibronectin, vitronectin, laminin-521, and collagen IV) were deposited on polydimethylsiloxane substrates with elastic moduli ranging from ~1 to 60 kPa using a high throughput protein plotter. Through our screening approach, we identified several non-intuitive protein-protein and protein-stiffness interactions and developed three novel culture substrates. hPSCs grown on these novel culture substrates displayed higher proliferation rates and pluripotency marker expression than current gold-standard culture substrates Geltrex- and vitronectin-coated plastic. This ECM microarray and screening approach is not limited to the factors studied here and can be broadly applied to other cell types to systematically screen microenvironmental conditions to optimally guide cell phenotype.